Clustering mechanism in the development of the regional economy and the involvement of small businesses in it - Manzura Bakhtiyorovna Beknazarova (THE INNOVATION ECONOMY, 2026)
The article analyzes the mechanism of clustering in the economy of the region, its structural structures and the theoretical-legal basis for attracting small businesses to the cluster system, as well as practical mechanisms. The inclusion of small businesses in the cluster is justified by the fact that it leads to modernization, competitiveness and growth of employment in the territory’s economy